Weevil Carbohydrate Intake Triggers Endosymbiont Proliferation: A Trade-Off between Host Benefit and Endosymbiont Burden - Elisa Dell’Aglio; Virginie Lacotte; Sergio Peignier; Isabelle Rahioui; Fadéla Benzaoui; Agnès Vallier; Pedro Da Silva; Emmanuel Desouhant; Abdelaziz Heddi; Rita Rebollo (mBio, 2023)
ABSTRACT Nutritional symbioses between insects and intracellular bacteria (endosymbionts) are a major force of adaptation, allowing animals to colonize nutrient-poor ecological niches. Many beetles feeding on tyrosine-poor substrates rely on a surplus of aromatic amino acids produced by bacterial endosymbionts. This surplus of aromatic amino acids is crucial for the biosynthesis of a thick exoskeleton, the cuticle, which is made of a matrix of chitin with proteins and pigments built from tyrosine-derived molecules, providing an important defensive barrier against biotic and abiotic stress. Other endosymbiont-related advantages for beetles include faster development and improved fecundity. The association between Sitophilus oryzae and the Sodalis pierantonius endosymbiont represents a unique case study among beetles: endosymbionts undergo an exponential proliferation in young adults concomitant with the cuticle tanning, and then they are fully eliminated. While endosymbiont clearance, as well as total endosymbiont titer, are host-controlled processes, the mechanism triggering endosymbiont exponential proliferation remains poorly understood. Here, we show that endosymbiont exponential proliferation relies on host carbohydrate intake, unlike the total endosymbiont titer or the endosymbiont clearance, which are under host genetic control. Remarkably, insect fecundity was preserved, and the cuticle tanning was achieved, even when endosymbiont exponential proliferation was experimentally blocked, except in the context of a severely unbalanced diet. Moreover, a high endosymbiont titer coupled with nutrient shortage dramatically impacted host survival, revealing possible environment-dependent disadvantages for the host, likely due to the high energy cost of exponentially proliferating endosymbionts. IMPORTANCE Beetles thriving on tyrosine-poor diet sources often develop mutualistic associations with endosymbionts able to synthesize aromatic amino acids. This surplus of aromatic amino acids is used to reinforce the insect’s protective cuticle. An exceptional feature of the Sitophilus oryzae/Sodalis pierantonius interaction is the exponential increase in endosymbiotic titer observed in young adult insects, in concomitance with cuticle biosynthesis. Here, we show that host carbohydrate intake triggers endosymbiont exponential proliferation, even in conditions that lead to the detriment of the host survival. In addition, when hosts thrive on a balanced diet, endosymbiont proliferation is dispensable for several host fitness traits. The endosymbiont exponential proliferation is therefore dependent on the nutritional status of the host, and its consequences on host cuticle biosynthesis and survival depend on food quality and availability.